Elite sprint swimmers' pre-season training techniques and content - Yakovlev, B. P.; Babushkin, G. D.; Rybin, R. E.; Bachin, V. P.; Apokin, V. V. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to substantiate the content and methods of elite sprint swimmers` pre-season training. Structure of the study. The study was conducted at the premises of the "Albatross" swimming pool in Omsk. Subject to the study were 20 elite sprint swimmers (CMS, MS) preparing for the Siberian Federal Area Championship (Barnaul, 2016). Conclusion. Elite sprint swimmers` pre-season training content and techniques have been developed. The pre-season training of swimmers includes the following four weekly micro-cycles: 1st - intensive (preferential development of aerobic endurance), 2nd - rehabilitative (primary development of anaerobic endurance), 3rd - intensive (primary development of aerobic endurance), 4th - rehabilitative (primary development of anaerobic endurance). The educational experiment under the study confirmed the benefits of the proposed training method for the swimmers` pre-season training, and it can be recommended for the elite swimmers` training process.